Need Help?

  • Notes
  • Comments & Questions

Evaluate \(I=\int x^{3} \cdot \sqrt{x^{2}+4} d x\)

case 2: \(\sqrt{a^{2}+x^{2}}\)

\(a^{2}=4 \rightarrow a=2\)

let \(x=a \tan \theta\)

\(d x=a \sec ^{2} \theta d \theta\)

\(\sqrt{x^{2}+4}=a \sec \theta\)

\(-\frac{\pi}{2} \le \theta \le \frac{\pi}{2}\)

let \(x=2 \tan \theta\)

\(d x=2 \sec ^{2} \theta d \theta\)

\(\sqrt{x^{2}+4}=2 \sec \theta\)

\(I=\int(2 \tan \theta)^3 \cdot 2 \sec \theta \cdot 2 \sec ^{2} \theta d \theta\)

\(I=\int 8 \tan ^{3} \theta \cdot 4 \sec ^{3} \theta d \theta\)

\(t=\sec \theta\)

\(1=32 \int \tan ^{2} \theta \sec ^{2} \theta \cdot(\tan \theta \cdot \sec a) d \theta\)

but \(\tan ^{2} \theta=\sec ^{2} \theta-1\)

\(I=32 \int\left(\sec ^{2} \theta-1\right) \cdot \sec ^{2} \theta(\sec \theta \tan \theta) d \theta\)

let \(t=\sec \theta \rightarrow d t=\sec \theta \tan \theta d \theta\)

\(I=32 \int\left(t^{2}-1\right) t^{2}(dt)=32 \int t^{4}-t^{2} d t\)

\(I=32\left[\frac{t^{5}}{5}-\frac{t^{3}}{3} \right]+{c}=32 t^{3}\left[\frac{t^{2}}{5}-\frac{1}{3}\right]+c\)

\(I=32 t^{3}\left[\frac{3 t^{2}-5}{15}\right]+c=\frac{32}{15} \,t^3\left[3 t^{2}-5\right)+c\)

\(\tan \theta=\frac{x}{2}\)

but I have \(t=\sec x=\frac{\sqrt{x^{2}+4}}{2}\)

\(I=\frac{32}{15}\left(\frac{\sqrt{x^{2}+4}}{2}\right)^{3}\left[3\left(\frac{\sqrt{x^{2}+4}}{2}\right)^{2}-5\right]+c\)

Evaluate \(\int \frac{d x}{\sqrt{x^{2}-a^{2}}} \:, a>0\)

\(\sqrt{x^{2}-a^{2}}\) case 2

\(x=a\sec \theta\)

\(d x=a \sec \theta \tan \theta d \theta\)

\(\sqrt{x^{2}-a^{2}}=a \tan \theta\)

\(0< \theta < \frac{\pi}{2} \text { or } \pi < \theta < \frac{3 \pi}{2}\)

\(\int \frac{d x}{\sqrt{x^{2}-a^{2}}}=\int \frac{a \sec \theta \tan \theta d \theta}{a \tan \theta}\)

\(=\int \sec \theta d \theta\)

\(=\ln |\sec \theta+\tan \theta|+C\)

\(x=a \sec \theta \rightarrow \sec \theta=\frac{x}{a}\)

\(\tan \theta=\frac{\sqrt{x^{2}-a^{2}}}{a}\)

\(\int \frac{d x}{\sqrt{x^{2}-a^{2}}}=\ln \left|\frac{x}{a}+\frac{\sqrt{x^{2}+a^{2}}}{a}\right|+c\)

\(=\ln \left|\frac{x+\sqrt{x^{2}+a^{2}}}{a}\right|+c\)

\(\ln \frac{a}{b}=\ln a-\ln b\)

\(\int \frac{d x}{\sqrt{x^{2}-a^{2}}}=\ln \left|x+\sqrt{x^{2}+a^{2}}\right|-\ln |a|+c\)

suppose that \(-\ln |a|+c=c_{1}\)

\(\int \frac{d x}{\sqrt{x^{2}-a^{2}}}=\ln \left|x+\sqrt{x^{2}+a^{2}}\right|+c_{1}\)

No comments yet

Join the conversation

Join Notatee Today!